Taking Stock of COVID-19 Labor Policy Responses in Developing Countries - De La Flor, Luciana; Mujica, Ingrid; Fontenez, Maria Belen; Newhouse, David; Rodriguez Alas, Claudia; Sabharwal, Gayatri; Weber, Michael (World Bank, Washington, DC, 2021)
This Jobs Watch brief provides an analysis of labor market and social protection responses to the COVID-19 crisis, with a focus on policies targeted to workers and firms. It includes a comprehensive set of labor market interventions, using data from the global COVID-19 SPJ Policy Inventory. The analysis can inform governments of approaches that can be taken when introducing or adapting their crisis mitigation measures. To our knowledge, this is the first summary of labor market policies adopted by developing countries in response to the COVID-19 crisis.